Changes of NT-proBNP and sST2 levels for predicting isolated episodes of ventricular tachyarrhythmias and electrical storm in patients with systolic heart failure and various implanted devices - A. Zh. Gasparyan; E. V. Guseva; G. S. Tarasovsky; S. Yu. Kashtanova; M. D. Utsumueva; T. V. Sharf; N. A. Mironova; S. F. Sokolov; V. P. Masenko; A. A. Skvortsov; N. B. Shlevkov (Российский кардиологический журнал, 2020)
Aim. To study the changes in N-terminal pro-brain natriuretic peptide (NT-proBNP) and growth stimulation gene-2 (sST2) to predict isolated episodes of ventricular tachyarrhythmias (VTA) and electrical storm (ES) in patients with systolic heart failure and implanted cardioverter-defibrillators, cardiac resynchronization therapy (CRT) defibrillators, as well as cardiac contractility modulation (CCM) devices.Material and methods. The study included 69 patients (mean, 59; women, 10; mean age, 59±13 years) with class I-III systolic HF and ischemic (n=36) or nonischemic (n=33) cardiomyopathy. The survey was carried out at baseline, as well as 1, 3, 6 and 12 months after device implantation. This included data collection, physical examination, determination of NT-proBNP and sST2, 6-minute walk test, electrocardiography (ECG), 24-hour Holter monitoring, echocardiography, assessment of device performance. Predictors of isolated VTA and ES were identified using ROC and multivariate analyzes.Results. According to the follow-up (median, 28 months) results, 3 groups of patients were formed: group 1 — without VTA (n=45); group 2 — isolated VTA (n=15); group 3 — ES (n=9). According to multivariate analysis, predictors of isolated VTA were as follows: 1) baseline NT-proBNP >3200 pg/ml; 2) minimum NTproBNP >1100 pg/ml during 12-month follow-up; 3) sST2 >26 ng/ml 3 months after device implantation; 4) presence of old myocardial infarction; 5) no echocardiographic signs of response to CRT or CCM therapy. There were following predictors of ES: 1) left ventricular end-systolic dimension >7,0 cm; 2) presence of VTA runs according to 24-hour Holter monitoring; 3) no echocardiographic signs of response to CRT or CCM therapy.Conclusion. The results obtained indicate that NT-proBNP and sST2 assessment in patients with systolic heart failure is promising for predicting isolated VTA, but not ES. Cardiac reverse remodeling as a result of effective CRT or CCM therapy is associated with a significant risk reduction for isolated VTA and ES.